Refractory hypokalemia – An exigent concern: Case series and review of literature - Gunadhar Padhi; Masood Ahmed Chandsha (Apollo Medicine)
Potassium is a major intracellular cation affecting tonicity and regulating intracellular processes such as protein/glycogen synthesis and carbohydrate metabolism and partially responsible for maintaining the potential difference across the membrane, particularly in excitable tissues such as nerve and muscle. Of all the electrolytes, a rapid change in potassium concentration is life-threatening. Hypokalemia is a common electrolyte disturbance, especially in hospitalized patients. Severe hypokalemia is life-threatening and requires urgent medical attention. It may trigger dangerous arrhythmias such as ventricular fibrillation and tachycardia, leading to cardiac arrest. It leads to neuromuscular weakness prolonging weaning in mechanically ventilated patients and also contributes to paralytic ileus. The body maintains serum potassium concentration within very narrow limits through tightly regulated feedback and feedforward systems. Understanding the physiology of potassium homeostasis and diverse etiologies of hypokalemia spanning from error in sample collection, endocrine abnormalities, renal tubular acidosis, and many more may guide toward the appropriate treatment of hypokalemia.